Japanese anime and women's gender-role changing - Yu, Shunyao (2015)
Feminism is a fast growing phenomenon in recent years. This paper started with the historical conflict of marriage and feminism, then researched the connection between anime and gender-role. Since Japanese anime was imported to China in 1980s, it has influenced the generation born in 1980s and 1990s in many aspects of their growth. These well-educated people perceived the Japanese culture and values through anime. This study connected gender stereotypes and marriage, and how Chinese well-educated anime fans interpret the gender-role portrayals from anime. Eight well-educated young people born in 1980s and 1990s participated in this study through semi-structured online interviews. This study not only tested their standard of choosing spouses, but also employed a qualitative method with cultivation theory. Furthermore, it introduced a new perspective of comparisons between females’ and males’ opinions of feminism. The result of this study has shown anime has a strong cultivation for participants’ recognition of both genders; Males and females have different views of the choice of work and marriage and the mismatch of male’s and female’s standards of choosing spouses. The outcome of this study suggests males need more awareness to put feminism in practice more than in theory.